Reconceptualizing Consumer Protection in Apartments: A Normative Analysis of Criminalization Practices by Property Developers in Indonesia - Rosa, Yenny; Mustofa, Muhammad; Chandra, Tofik Yanuar (Advances In Social Humanities Research, 2025)
This study examines the emerging phenomenon of consumer criminalization in Indonesia's high-rise housing sector, where property developers increasingly utilize criminal law mechanisms to exert pressure on buyers involved in contractual disputes. While previous studies have largely focused on issues of unfair contract terms, late delivery, and imbalanced bargaining positions, the use of criminal law as a tool of intimidation remains significantly underexplored. Employing a normative legal research approach, this study analyzes statutory frameworks, judicial decisions, and scholarly literature to investigate the structural and normative weaknesses that allow criminalization to occur. The findings reveal that the misuse of defamation and embezzlement provisions represents a systemic distortion of the ultimum remedium principle and indicates a broader imbalance in the legal power relationship between developers and consumers. This study argues that current regulatory mechanisms are insufficient to prevent the instrumentalization of criminal law in what is fundamentally a civil contractual relationship. By integrating perspectives from global theories of overcriminalization, substantive justice, and consumer protection, the research provides a conceptual foundation for reconstructing Indonesia's legal framework. The study concludes by proposing regulatory reforms, institutional strengthening, and procedural guidelines to ensure that criminal law is not deployed as an oppressive tool against consumers. This contributes to the global discourse on proportionality in criminal law and the protection of vulnerable parties in modern housing markets.